Classroom Action Research on Digital Interactive Learning for Arabic Speaking Development in Islamic Junior High Schools - Habib, Moh. Tohiri (Al-Muhawaroh: Jurnal Pendidikan Bahasa Arab, 2025)
The rapid advancement of digital technology offers new opportunities for transforming language education, yet developing Arabic speaking proficiency (Maharah Kalam) remains a significant challenge in Islamic junior high schools. This study aims to evaluate the effectiveness of interactive digital learning media in enhancing Arabic speaking skills among Grade 8 students at Madrasah Tsanawiyah Darullughah Wadda’wah (MTs Dalwa). Employing a quasi-experimental design, 30 students were purposively selected and divided equally into an experimental group and a control group. The experimental group engaged with AI-assisted pronunciation tools, gamification-based vocabulary learning applications, and augmented reality (AR) conversation simulations, while the control group received traditional textbook-based instruction and teacher-led drills. Data were collected using pre- and post-tests to assess speaking proficiency (covering fluency, pronunciation, vocabulary usage, and grammatical accuracy), complemented by classroom observations and semi-structured interviews with students and teachers. The findings revealed that the experimental group exhibited a statistically significant improvement, with a 32.5% increase in post-test scores compared to a 12.3% improvement observed in the control group. Additionally, qualitative feedback indicated that students experienced higher engagement, reduced speaking anxiety, and enhanced motivation. Despite these positive outcomes, challenges such as technical limitations and the need for structured teacher training were noted. In conclusion, the integration of interactive digital tools in Arabic language instruction can effectively enhance speaking proficiency, bridging the gap between theoretical knowledge and practical communication skills in Islamic educational settings. Further research is recommended to address implementation challenges and explore long-term retention effects.